Estimating the impact of metro north - Edgar Morgenroth (The Economic and Social Research Institute (ESRI), 2009)
The single largest project under the Irish National Development Plan (NDP) 2007-2013, is the construction of a Metro system. Despite the fact that this is the largest project under the NDP and the government's transport strategy, Transport 21, no cost benefit analysis on the project has been published. This paper aims at addressing this lack of published analysis by considering the likely economic impact one of the Metro projects, Metro-North. In doing so the paper implements two novel methods namely the use of estimates from hedonic house price models and the results from macroeconomic studies instead of the conventional cost-benefit analysis. The two methods come up with contradictory results in that the hedonic pricing methodology would suggest that the Metro-North project should not proceed while the macroeconomic approach suggests the investment should go ahead. These results are dependent on the underlying assumptions, excluded benefits and parameters used, but given the analysis in the paper alternatives can be implemented readily.
Keywords: H43; H54; R42; R53; 330; Metro North; impact assessment; Infrastrukturinvestition; Schienenpersonennahverkehr; Projektbewertung; Hedonischer Preisindex; Gesamtwirtschaftliche Investitionstheorie; Irland